1989
DOI: 10.1037/h0099527
|View full text |Cite
|
Sign up to set email alerts
|

Involving consumers in the discharge process.

Abstract: It is clear to those involved in psychosocial rehabilitation that consumers inherently have the ability to effectively communicate with each other and to be supportive of those who have experienced life in psychiatric hospitals. This article will describe an innovative model for consumers providing into-hospital reach-out and will discuss why participants in self-help clubhouse programs are ideally suited for involvement in the hospital discharge process.This document is copyrighted by the American Psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The approach to service provi sion in these models focuses on explor ing an individual's abilities as they relate to dealing with a particular illness and to living and working in the com munity. Ideally, the support offered by staff members contributes to recovery, a complex process through which con sumer/survivors gain mastery over their illness (Anthony, 1993;Deegan, 1988 Shelton & Rissmeyer, 1989). In the United States a review by the Human Resource Association of the Northeast found increasing activity in this area, with a majority of states indicating that funding would be in creased in coming years (Specht, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The approach to service provi sion in these models focuses on explor ing an individual's abilities as they relate to dealing with a particular illness and to living and working in the com munity. Ideally, the support offered by staff members contributes to recovery, a complex process through which con sumer/survivors gain mastery over their illness (Anthony, 1993;Deegan, 1988 Shelton & Rissmeyer, 1989). In the United States a review by the Human Resource Association of the Northeast found increasing activity in this area, with a majority of states indicating that funding would be in creased in coming years (Specht, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, these can be grouped into two closely related areas: attempts to improve elements of basic social support such as housing and income, and new approaches to providing mental health services (of which the various components of psychosocial rehabilitation are the most prominent) (Kaufmann, 1995; Wollert, 1986). Perhaps the most striking feature of these new service models is their recognition of the capacities of individual consumer/survivors (Carling, 1993; Chamberlin, Rogers & Ellison, 1996; Macnaughton, 1992; Rapp, Shera & Kisthardt, 1993; Segal, Silverman & Temkin, 1993; Shelton & Rissmeyer, 1989). The approach to service provision in these models focuses on exploring an individual's abilities as they relate to dealing with a particular illness and to living and working in the community.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last decade has seen an increase in opportunities for people with psychiatric disabilities to become service providers. In mental health agencies across the country, people with psychiatric disabilities have been hired as case managers (Manning & Suire, 1996; Sherman & Porter, 1991; Solomon & Draine, 1995), vocational support specialists (Mowbray, Moxley, & Collins, 1998), consumer advocates (Dixon, Krauss, & Lehman, 1994), and outreach workers (Fisk, Rowe, Brooks, & Gildersleeve, 2000; Shelton & Rissmeyer, 1989). In addition, in recent years there has been an increase in the number of consumer-run services (Mowbray & Tan, 1993; Torrey, Mead, & Ross, 1998; Van Tosh & del Vecchio, 2000).…”
mentioning
confidence: 99%